Essential health information available for India in the public domain on the internet - Dandona Rakhi; Raban Magdalena Z; Dandona Lalit (BMC, 2009)
Abstract Background Health information and statistics are important for planning, monitoring and improvement of the health of populations. However, the availability of health information in developing countries is often inadequate. This paper reviews the essential health information available readily in the public domain on the internet for India in order to broadly assess its adequacy and inform further development. Methods The essential sources of health-related information for India were reviewed. An extensive search of relevant websites and the PubMed literature database was conducted to identify the sources. For each essential source the periodicity of the data collection, the information it generates, the geographical level at which information is reported, and its availability in the public domain on the internet were assessed. Results The available information related to non-communicable diseases and injuries was poor. This is a significant gap as India is undergoing an epidemiological transition with these diseases/conditions accounting for a major proportion of disease burden. Information on infrastructure and human resources was primarily available for the public health sector, with almost none for the private sector which provides a large proportion of the health services in India. Majority of the information was available at the state level with almost negligible at the district level, which is a limitation for the practical implementation of health programmes at the district level under the proposed decentralisation of health services in India. Conclusion This broad review of the essential health information readily available in the public domain on the internet for India highlights that the significant gaps related to non-communicable diseases and injuries, private health sector and district level information need to be addressed to further develop an effective health information system in India.